ANDROID-BASED ADMINISTRATIVE SYSTEM DEVELOPMENT AT TACHFIDZHUL QUR'AN BOARDING SCHOOL PONDOK AL MUKHLISH KALIDADI CENTRAL LAMPUNG - Huda, Muhammad (YHMM PUBLISHING, 2024)
Along with the development of the digital era, all human needs require technology. One of the tools for everyday human needs is the internet, which is an online global network without any boundaries that provides all types of information and system development in the current era of globalization. Al Mukhlish Kalidadi Islamic Boarding School, Kalirejo, Lampung is currently in the stage of management arrangements and wants to always develop using digital. The current developments have made the spirit and want to always be at the forefront of the field of religious sciences, especially regulating management in the administrative field, therefore the availability of facilities and performance to facilitate the administration of santri administration, especially the payment administration of everything in the pesantren, therefore in here the author will develop an existing administrative system to make it easier to process the management. In this study, the method used is in the form of R&D which will develop and test its effectiveness by expert experts. While data collection uses observation, interview and literature study. The conclusions obtained in this study are to reorganize the management of the boarding schools, especially in the administration sector so that all data can be safe and easy to use.